PEMURNIAN BEBERAPA JENIS LEMAK TENGKAWANG DAN SIFAT FISIKO KIMIA - Raden Esa Pangersa Gusti; Zulnely (Jurnal Penelitian Hasil Hutan, 2015)
Illipe nut in Indonesia serves as one of the essential export commodities from non-wood forest products group. Illipe nut through the extraction can be processed into high-economic valued fat that could function as cocoa butter substitute (CBS), obtained through extraction of illipe nut Illipe nut's fat that results from extraction process can not be directly used, but should be previously refined. In this study, refining of illipe nut's fat was conducted through degumming and neutralization process. Degumming process was carried out by adding acids (acetic, citric and phosphoric) each with 20% strength at 0,4% (w/w) to the fat that has been previously heated. The results showed that degumming using phosphoric acid produced a better quality fat compared to that with citric acid and acetic acid. NaOH was used for neutralization process. The resulting neutralized fat was then examined for its physical-chemical properties which revealed that such properties were not so far different from those of commercial illipe nut's fat. The GC analysis as conducted on the refined illipe nut's fat showed that it consisted of various saturated fatty acid as well as unsaturated and other chemical compounds. All of the examined illipe nut's fat in this research showed that oleic acid is the dominant component.